Brain transcriptomes and plasma proteins reveal upregulation of a proinflammatory signature in APOE e4 carriers: Genetics: Genetics and omics of AD II. (7th December 2020) - Das, Sudeshna; Serrano‐Pozo, Alberto; Li, Zhaozhi; Kivisäkk, Pia; Carlyle, Becky C.; Arnold, Steven E; Hyman, Bradley T.
Abstract: Background: APOE e4 —the main genetic risk factor for Alzheimer's disease (AD)—is associated with an increased Aβ plaque burden. Aβ plaques are surrounded by activated microglia, but whether APOE influences microglial responses to plaques in human brains has not yet been extensively studied. In this study, we investigated whether APOE alleles are associated with differences in microglial gene expression—either in concert with, or independent of, AD neuropathological changes—and with plasma protein levels. Method: We analyzed brain transcriptomics data from the Mount Sinai Brain Bank (MSBB) and the Rush Religious Orders Study and Memory and Aging Project (ROSMAP). We performed integrative analysis to evaluate microglia gene expression across all APOE alleles: e4+ (e3/e4, e4/e4), e2+ (e2/e2, e2/e3) and e3/e3 (reference), adjusting for Braak neurofibrillary tangle (NFT) stage and CERAD neuritic plaque (NP) score. Additionally, we investigated the effect of the e4 allele on the plasma levels of 400 proteins in 34 cognitively normal subjects, measured using the Olink TM Proximity Extension Assay (PEA) panels. Result: More than a third of the microglial genes were significantly upregulated in e4+ individuals controlling for CERAD NP score. Sensitivity analysis using Braak NFT stage yielded similar results. These genes included complement factors ( C3, PLAU, PLAUR ), Toll‐like receptor ( TLR2, TLR5, TLR7, SPP1 ), and chemokines ( CCL2, CCR5, CCR10 ). Of note, ∼20% of these genes were significantly increased even in cognitively normal e4+ subjects with low AD neuropathological changes at autopsy (none or sparse NP and Braak NFT stage 0‐II), suggesting e4 is associated with an enhanced baseline inflammatory pattern. A similar pro‐inflammatory profile was also observed in the plasma of cognitively normal e4+ carriers. Conclusion: Our brain transcriptomic analyses and multiplexed quantification of plasma proteins indicate that carrying the APOE e4 allele is associated with a pro‐inflammatory program compared to the APOE e3/e3 reference group. This differential effect of the APOE e4 allele was observed in brains of individuals with low AD neuropathological changes at autopsy, suggesting that it is not just mediated through its effects on amyloid plaques. Thus, APOE e4 may prime microglia toward a pro‐inflammatory phenotype before plaques and tangles develop.